Olympic Games Legacy: Sports Facilities and Related Infrastructure as a Factor of Long-Term Regional Economic Dynamics - Nikolay V. GONTAR; Valentina I. ODINTSOVA (Communications of International Proceedings, 2020)
Olympic Games Legacy is often a significant problem for cities hosting the Olympics or FIFA Championships. At the same time, the formation of an extensive sports and non-sports infrastructure makes it possible to include the Olympic Games Legacy in the economic processes and social development of the cities where events are held. The article examines the example of Sochi, the host city of the XXII Winter Olympic Games in 2014, and analyzes the model that made the Olympic Games Legacy an element of urban sustainability. The article discusses the transformation of economic and non-economic factors in the use of Olympic Games Legacy. It also analyzed the change in the role of the Legacy in shaping the economic trajectory at three stages: before the start of the covid-19 pandemic, during the period of restrictions associated with the pandemic, and during the projected recovery from the crisis. The position of the city as an all-Russian resort is considered as the basis for the model of inclusion of the Olympic Games Legacy in Sochi in the processes of sustainable development of the city and the region. This made it possible to fully use the transport, engineering and other related infrastructure built for the Olympics, and also made it possible to maintain the functionality of sports facilities. These processes are analyzed in the article taking into account the multi-level dynamics of tourist visits in the world, Russia and Sochi in the period before the pandemic and in 2020. In addition, in relation to modern conditions, measures of state support for tourism as a key economic sector for Sochi are considered. Such measures are seen as an important tool for supporting the Olympic Games Legacy and preserving the role of its sporting elements as a factor in the economic development of Sochi.
Keywords: Olympic Games Legacy; Sport; Tourism; Sochi; Regional Politics.